Analysis of Factors Affecting Driving Safety at PT. Cakraindo Mitra International - Numang, Irpan (Universitas Sulawesi Barat, 2025)
This study aims to analyze the effect of safety briefings, work experience, and work breaks on driving safety among truck drivers at PT Cakraindo Mitra Internasional. The background of this study stems from the high number of traffic accidents at the company from January to April 2025, most of which were caused by driver negligence. This study uses a quantitative method with a cross-sectional approach. The research sample consisted of 43 respondents selected using purposive sampling techniques according to the minimum criteria of two trips. Data were collected through a questionnaire based on a 1–5 Likert scale, then analyzed using the Partial Least Square – Structural Equation Modeling (PLS-SEM) method. The results showed that safety briefings, work experience, and work breaks had a positive and significant effect on driving safety, both partially and simultaneously. These findings indicate that regular safety briefings, adequate work experience, and good quality rest can improve safe driving behavior. This study recommends that companies consistently strengthen their safety briefing programs, effectively manage drivers' work and rest schedules, and utilize work experience as a resource for safety training